1999
DOI: 10.1038/sj.onc.1202297
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 Associates with the TBP-associated factor TAFII250 to regulate Sp1-mediated transcription

Abstract: We have previously shown that Sp1-mediated transcription is stimulated by Rb and repressed by cyclin D1. The stimulation of Sp1 transcriptional activity by Rb is conferred, in part, through a direct interaction with the TBP-associated factor TAF II 250. Here we investigated the mechanism(s) through which cyclin D1 represses Sp1. We examined the ability of cyclin D1 to regulate transcription mediated by Gal4-Sp1 fusion proteins, which contain the Gal4 DNA-binding domain and Sp1 trans-activation domain(s). The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 49 publications
1
50
0
Order By: Relevance
“…Thus, glucosamine may also have augmented transcriptional activation by Sp1 or affected interactions between Sp1 and other proteins. There are 4 transcriptional activation domains in Sp1 that interact with transcriptional cofactors, including subunits of the TF II D and CRSP complexes (70)(71)(72)(73). Recognized interactions between Sp1 and Smads (74), AP-1 (78), retinoblastoma protein (60,76), cyclin D (70), CBP/p300 (through progesterone receptors) (77), or other Sp1 molecules to form higher-order multimers (71) could all have been affected by glucosamine and merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, glucosamine may also have augmented transcriptional activation by Sp1 or affected interactions between Sp1 and other proteins. There are 4 transcriptional activation domains in Sp1 that interact with transcriptional cofactors, including subunits of the TF II D and CRSP complexes (70)(71)(72)(73). Recognized interactions between Sp1 and Smads (74), AP-1 (78), retinoblastoma protein (60,76), cyclin D (70), CBP/p300 (through progesterone receptors) (77), or other Sp1 molecules to form higher-order multimers (71) could all have been affected by glucosamine and merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Such a model would be supported by the possibility that Rb and cyclin D1 may bind to overlapping sites at the N-terminus of TAF II 250 (Figure 1). It has been previously reported that in co-infection assays, an increasing dose of an Rb-expressing baculovirus, co-infected with baculoviruses expressing TAF II 250 and cyclin D1, could apparently reduce the amount of cyclin D1 and TAF II 250 found complexed following immunoprecipitation (Adnane et al, 1999). This result suggested that Rb was competing with cyclin D1 for binding to TAF II 250.…”
Section: Binding Of Cyclin D1 To Rb Is Not Required To Block Rb-mediamentioning
confidence: 60%
“…It has also been demonstrated that cyclin D1 is able to bind to the amino terminus of hTAF II 250 (Adnane et al, 1999), though these latter studies were performed primarily through co-transfection assays and not with puri®ed proteins. We examined the Rb-and TAF II 250-binding properties of puri®ed cyclin D1 in vitro, using a baculovirus-expressed, GST-tagged, murine cyclin D1 protein.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations